Avaliação da qualidade de vida relacionada à saúde bucal de crianças e adolescentes com artrite idiopática juvenil - Santos, Débora Rejane dos (2014)
Juvenile idiopathic arthritis (JIA) is the most common chronic disease of the connective tissue in children and adolescents, being related to impaired health-related quality of life. Among the various complications related to JIA are oral diseases such as caries and periodontal disease, whose risk of development is higher due to factors such as the involvement of the temporomandibular joint, difficulty in performing oral hygiene when the joints of the upper limbs are involved, and use of oral medication containing sugar. However, the extent to which oral diseases interfere with the daily life and well-being of children and adolescents affected is unknown. The aim of this study was to assess the correlation between oral health indicators and oral health-related quality of life (OHRQoL) of children and adolescents with juvenile idiopathic arthritis (JIA) according to their caregivers perceptions. Two groups of adults filled the short form of the Brazilian Parental-Caregiver Perceptions Questionnaire (SF: 13 B-PCPQ), which assesses OHRQoL. These groups were as follows: parents or guardians [mean age, 40.6 years; standard deviation (SD) = 10.97 years] of healthy children and adolescents (n = 15; mean age, 10.7 years; SD = 2.16) and parents or guardians of children and adolescents with JIA (n = 17; mean age, 9.8 years; SD = 2.86), early-onset oligoarticular (n = 8), systemic (n = 5), or polyarticular (n = 4). Dental evaluations were performed on all children and adolescents in the study. There was no significant difference in SF: 13 B-PCPQ scores of the two groups. Children and adolescents with JIA had fewer caries in their primary dentition and more gingival bleeding after probing than those without JIA. The frequency of temporomandibular disorders was 50.0% for JIA patients and 46.7% for their healthy counterparts. There was no correlation between oral health indicators and SF: 13 B-PCPQ scores. As perceived by caregivers, JIA did not negatively impact the well-being of their children and adolescents as related to oral health, and their OHRQoL did not correlate with their oral health status.